Upaya Pencegahan Perilaku Konsumtif Melalui Layanan Informasi Menggunakan Teknik Audio Visual - Sri Ngayomi Yudha Wastuti; Amir Husin Pangaribuan (Program Studi Bimbingan Penyuluhan Islam Fakultas Dakwah dan Komunikasi, 2020)
This research is motivated by the development of globalization, which has an extraordinary impact on adolescents. Adolescence is a period where they want to be accepted by their existence and recognized by their existence so that they do everything to fulfill their desires. Adolescence is the process of finding identity, so that makes them more easily influenced and carried away by their environment. The need to be accepted and be the same as other people causes teens to follow various attributes that are popular. One way is to behave consumptively. The formation of consumptive behavior in human beings can be influenced by two factors originating from within the individual (internal) and from outside the individual (external). This study was included in the Quasi Experiment with one group design; the population in this study were MAN 1 Medan students. The sample is class X students of 25 people selected by using purposive sampling technique. The instrument used was a questionnaire with a Likert scale model. The validity test of the research instrument was through the content validity test by several experts and was also carried out using Product Moment Correlation with the mean correlation coefficient of 0.656 and the reliability test using the Cronbach Alpha formula with r 0.972.